1984
DOI: 10.1080/14640748408402190
|View full text |Cite
|
Sign up to set email alerts
|

Win-Stay Behaviour in the Rat

Abstract: The Law of Effect dictates that animals will repeat the just-reinforced response “win-stay”, and yet there have been apparent violations of this by rats running for food in mazes, in the form of “win-shift” behaviour. Four experiments analysed the conditions determining win-stay and win-shift behaviour. All the experiments employed a schedule in which reinforcement was distributed across two choices, and in which the probability of reinforcement for the first response after previous reinforcement was equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…It is difficult to compare the accuracies of rats in a T-maze with those in an operant box, because the rats are unable to use orienting cues to facilitate bridging the ITI in a T-maze. Because this task requires memory for the last response and its consequence, the T-maze procedure may be disruptive, because it involves moving the animal from the goal box to the start box between trials and involves a longer delay between the choice response and reinforcement (see Evenden & Robbins, 1984;Gittis et al, 1988;Haig et al, 1983). Thus, the present comparison of rats responding with a nose-poke in an operant chamber offers the most similar comparison to pigeons pecking.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is difficult to compare the accuracies of rats in a T-maze with those in an operant box, because the rats are unable to use orienting cues to facilitate bridging the ITI in a T-maze. Because this task requires memory for the last response and its consequence, the T-maze procedure may be disruptive, because it involves moving the animal from the goal box to the start box between trials and involves a longer delay between the choice response and reinforcement (see Evenden & Robbins, 1984;Gittis et al, 1988;Haig et al, 1983). Thus, the present comparison of rats responding with a nose-poke in an operant chamber offers the most similar comparison to pigeons pecking.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, when rats were trained in a T-maze to win-stay (i.e., to return to the same arm) versus win-shift, they initially showed a bias to shift, visiting the previously unvisited arm early in training and showing reduced accuracy (Haig, Rawlins, Olton, Mead, & Taylor, 1983); this pattern of results has been found in adult rats in a T-maze (Haig et al, 1983), as well as in young rats in a Y-maze (Gittis et al, 1988). Additionally, an experiment by Evenden and Robbins (1984), training rats in either an operant box with levers or a Y-maze, indicated that the rats in the operant chamber initially tended to stay, whereas the rats in a Y-maze showed a high level of shift behavior that changed to stay behavior with training. These results suggest that rats' response biases are flexible with training but show different initial levels of stay and shift behavior, depending on the apparatus.…”
mentioning
confidence: 93%
“…Our current knowledge of molecular pat-terns of responding on simple concurrent and concurrent-chains schedules may be summarized as follows: When the probability of reinforcement is independent of the location of the previous reinforcer, such as occurs when interdependent scheduling is used, positive recency or win-stay behavior occurs on simple concurrent schedules (Evenden & Robbins, 1984;Menlove, 1975;Morgan, 1974;Shimp, 1966) whereas a transient elevation in preference for the key with the shorter terminal link occurs on concurrent-chains schedules (at least with equal initial links). When the probability of reinforcement does depend on the location of the previous reinforcer, as in the case of independent scheduling, negative recency or win-shift behavior is observed on concurrent-chains schedules, whereas the only evidence to date indicates that in simple concurrent schedules relative response rate is independent of which response was just reinforced (Nevin, 1969 (Figures 2, 3, 5, and 7), raises the possibility that the molar initiallink effect might be an artifact of schedule duration.…”
Section: Inspection Ofmentioning
confidence: 99%
“…Additional evidence that relative response rate in the initial links of a concurrent-chains schedule may vary systematically with time within a given exposure to the initial links is provided by the existence of nonuniform relative response rates on simple concurrent schedules. Evenden and Robbins (1984), Menlove (1975), Morgan (1974), and Shimp (1966) all reported a positive recency effect of reinforcement on immediately subsequent responding. Menlove, using a standard concurrent VI VI schedule, found that the relative frequency of responding, calculated with respect to the key with the higher density of reinforcement, was elevated in the first 5 s following reinforcement on the high-density key whereas the relative response rate during the first 5 s after reinforcement on the low-density key was either depressed or equal to its overall average value.…”
mentioning
confidence: 99%
“…Adequate explanations for radial maze behavior are likely to be based on a combination of ecological (Olton, 1982;Yoerg & Kamil, 1982), cognitive (Olton, 1982;Roberts, 1984), and learning-theory (Evenden & Robbins, 1984; Gaffan et aI., 1983) factors.…”
mentioning
confidence: 99%